OLD TESTAMENT PROPHETS AND THE CALL FOR A CORRUPTION FREE SOCIETY - Kakkanattu, Joy Philip (Asian Horizons, 2012)
An important component of the Old Testament Prophetic movement is its uncompromising demand for a just society where relationship between man and God is intrinsically measured by and correspondent to the right relationship between man and man. At a time when the institution of monarchy jeopardized the Exodus and the covenant vision of a society based on principle, justice, equality and love to promote the economics of affluence and triumphalism without listening to the cry of the marginalised of the society, the prophets arose to become the voice of the voiceless and took care that the ideals of the Exodus and Covenant be remembered. They raised their voices against the corruption, exploitation and injustice prevalent in their society and stood for the cause of the poor and the vulnerable. Pleading benevolence for the marginalised, they envisaged a new society, where the poor and needy get equal social and legal protection.2 A corollary of this theme is the prophetic criticism of corruption existing in various strata of societal relationships. It may not be a hyperbole to consider the biblical prophets, both classical and pre-classical, as great anti-corruption crusaders against all evasions and erosions in moral, religious and societal living.